2021
DOI: 10.1111/jocn.15958
|View full text |Cite
|
Sign up to set email alerts
|

Approaches of male nurses for degendering nursing and becoming visible: A metasynthesis

Abstract: Introduction: Patient, nurse and public discrimination against male nurses is welldocumented. Male nurses encounter challenges in degendering nursing and becoming more visible nursing professionals. However, little is known about male nurses' decisions and strategies to address issues concerning gender-based discrimination and professional visibility. Aims:To develop a comprehensive understanding of the approaches of male nurses to degender nursing and become more visible in the profession.Methods: A metasynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…Such finding might be due to social and cultural factors such as males are more eager to have prestigious practice, so they tend to seek managerial/leading work rather than providing direct patient care, while females found tend to be more involved in patient care practice. This finding goes partially in accordance with previous studies 35,44,49 . In this context, Younas et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Such finding might be due to social and cultural factors such as males are more eager to have prestigious practice, so they tend to seek managerial/leading work rather than providing direct patient care, while females found tend to be more involved in patient care practice. This finding goes partially in accordance with previous studies 35,44,49 . In this context, Younas et al.…”
Section: Discussionsupporting
confidence: 93%
“…This finding goes partially in accordance with previous studies. 35,44,49 In this context, Younas et al reported that such negative perception might be due to poor social recognition of nursing as a dignified and respectful profession, and equal to other professions. 44 Regarding nurses' qualification, the findings of the current study disclosed that nurses' qualification was positively association with their perception of QNC, although it was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age was negatively associated with behavioural identity and not with cognitive and emotional identity for both genders. This may imply that finding ways to maintain their behavioural identity after their graduation from school was a key point in solving the challenge of attrition among male nurses within four years of starting their careers [ 1 , 18 , 19 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to female nurses, turnover rates are higher and retention times are shorter among male ones [ 34 , 35 , 36 ]. College education is critical to PI formation among male nursing students; if they are educated to have a higher sense of nursing PI, they can also have a better nursing career trajectory [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%